Characterization of a bacteriophage with broad host range against strains of Pseudomonas aeruginosa isolated from domestic animals - de Melo, Anna Cristhina Carmine; da Mata Gomes, Amanda; Melo, Fernando L.; Ardisson-Araújo, Daniel M. P.; de Vargas, Agueda Palmira Castagna; Ely, Valessa Lunkes; Kitajima, Elliot W.; Ribeiro, Bergmann M.; Wolff, José Luiz Caldas (BMC microbiology, 2019)
Background Pseudomonas aeruginosa is an opportunistic pathogen and one of the leading causes of nosocomial infections. Moreover, the species can cause severe infections in cystic fibrosis patients, in burnt victims and cause disease in domestic animals. The control of these infections is often difficult due to its vast repertoire of mechanisms for antibiotic resistance. Phage therapy investigation with P. aeruginosa bacteriophages has aimed mainly the control of human diseases. In the present work, we have isolated and characterized a new bacteriophage, named Pseudomonas phage BrSP1, and investigated its host range against 36 P. aeruginosa strains isolated from diseased animals and against P. aeruginosa ATCC strain 27853. Results We have isolated a Pseudomonas aeruginosa phage from sewage. We named this virus Pseudomonas phage BrSP1. Our electron microscopy analysis showed that phage BrSP1 had a long tail structure found in members of the order Caudovirales. “In vitro” biological assays demonstrated that phage BrSP1 was capable of maintaining the P. aeruginosa population at low levels for up to 12 h post-infection. However, bacterial growth resumed afterward and reached levels similar to non-treated samples at 24 h post-infection. Host range analysis showed that 51.4% of the bacterial strains investigated were susceptible to phage BrSP1 and efficiency of plating (EOP) investigation indicated that EOP values in the strains tested varied from 0.02 to 1.72. Analysis of the phage genome revealed that it was a double-stranded DNA virus with 66,189 bp, highly similar to the genomes of members of the genus Pbunavirus , a group of viruses also known as PB1-like viruses. Conclusion The results of our “in vitro” bioassays and of our host range analysis suggested that Pseudomonas phage BrSP1 could be included in a phage cocktail to treat veterinary infections. Our EOP investigation confirmed that EOP values differ considerably among different bacterial strains. Comparisons of complete genome sequences indicated that phage BrSP1 is a novel species of the genus Pbunavirus . The complete genome of phage BrSP1 provides additional data that may help the broader understanding of pbunaviruses genome evolution.